Angiogenin and the MMP9‐TIMP2 axis are up‐regulated in proangiogenic, decidual NK‐like cells from patients with colorectal cancer. Issue 10 (15th May 2018) - Bruno, Antonino; Bassani, Barbara; D'Urso, Davide Giuseppe; Pitaku, Ilvana; Cassinotti, Elisa; Pelosi, Giuseppe; Boni, Luigi; Dominioni, Lorenzo; Noonan, Douglas M.; Mortara, Lorenzo; Albini, Adriana
ABSTRACT: NK cells are effector lymphocytes involved in tumor immunosurveillance; however, in patients with solid malignancies, NK cells have compromised functions. We have previously reported that lung tumor‐associated NK cells (TANKs; peripheral blood) and tumor‐infiltrating NK cells (TINKs) show proangiogenic, decidual NK‐like (dNK) phenotype. In this study, we functionally and molecularly investigated TINKs and TANKs from blood and tissue samples of patients with colorectal cancer (CRC), a neoplasm in which inflammation and angiogenesis have clinical relevance, and compared them to NK cells from controls and patients with nononcologic inflammatory bowel disease. CRC TINKs/TANKs showed decreased expression for the activatory marker NKG2D, impaired degranulation activity, a decidual‐like NK polarization toward the CD56 bright CD16 dim/− CD9 + CD49 + subset. TINKs and TANKs secreted cytokines with proangiogenic activities, and induce endothelial cell proliferation, migration, adhesion, and the formation of capillary‐like structures in vitro. dNK cells release specific proangiogenic factors; among which, angiogenin and invasion‐associated enzymes related to the MMP9‐TIMP1/2 axis. Here, we describe, for the first time, to our knowledge, the expression of angiogenin, MMP2/9, and TIMP by TANKs in patients with CRC. This phenotype could be relevant to the invasive capabilities and proangiogenic functions of CRC‐NK cells and become a novel biomarker. STAT3/STAT5 activation was observed in CRC‐TANKs, and treatment with pimozide, a STAT5 inhibitor, reduced endothelial cell capability to form capillary‐like networks, inhibiting VEGF and angiogenin production without affecting the levels of TIMP1, TIMP2, and MMP9, indicating that STAT5 is involved in cytokine modulation but not invasion‐associated molecules. Combination of Stat5 or MMP inhibitors with immunotherapy could help repolarize CRC TINKs and TANKs to anti‐ tumor antimetastatic ones.—Bruno, A., Bassani, B., D'Urso, D. G., Pitaku, I., Cassinotti, E., Pelosi, G., Boni, L., Dominioni, L., Noonan, D. M., Mortara, L., Albini, A. Angiogenin and the MMP9‐TIMP2 axis are up‐regulated in proangiogenic, decidual NK‐like cells from patients with colorectal cancer. FASEB J. 32, 5365–5377 (2018). www.fasebj.org